Volume reduction of the evaporator concentrate for incorporation in cement (Brazilian Journal of Radiation Sciences, 2021)
This study evaluates different routes of drying and cementation of Evaporator Concentrate (EC) from nuclear reactors. The Pressurized Water Reactor is one of the most used in nuclear power plants, and it uses boric acid as a coolant to control the nuclear fission. When the boric acid solution  loses its characteristics, it is directed to an evaporation system, generating the EC. The cementation is used as a technique to immobilize this kind of waste, due to the low cost and ease of use of the cement, in addition to its good stability and mechanical strength. However, the EC is a liquid solution, which leads to a high volume of wastes. The inclusion of a drying step might be advantageous in providing a reduction of the EC volume to be solidified, consequently reducing the number of packings generated. The tests were performed at the Laboratório de Cimentação at CDTN. The equipment chosen for the drying was the lab-oven, because it is easy to use and enables a full drying at relatively low temperatures. The cementation was carried out with different amounts of dry EC incorporated and with various water/cement matrix (a/cm) relations. As established by the norm CNEN NN 6.09, the compressive strength of homogeneous cementitious products, with 28 days of curing, must be greater than or equal to 10MPa for a safe disposal of the radioactive wastes. Formulations with a/cm between 0,25 and 0,27 and incorporation of dry EC between 10% and 20% showed the best results so far.
Keywords: evaporator concentrate; volume reduction; cementation